2018
DOI: 10.2903/j.efsa.2018.5494
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological analyses of African swine fever in the European Union (November 2017 until November 2018)

Abstract: This update on the African swine fever (ASF) outbreaks in the EU demonstrated that out of all tested wild boar found dead, the proportion of positive samples peaked in winter and summer. For domestic pigs only, a summer peak was evident. Despite the existence of several plausible factors that could result in the observed seasonality, there is no evidence to prove causality. Wild boar density was the most influential risk factor for the occurrence of ASF in wild boar. In the vast majority of introductions in do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(139 citation statements)
references
References 56 publications
4
135
0
Order By: Relevance
“…Term of Reference 3 (TOR3) requested a review of the control measures applied by affected MSs to control the spread of ASF in wild boar and to eradicate infection. In the previous reporting period (EFSA, ), this assessment was based on a spatiotemporally explicit individual‐based model approach in structured geographic landscapes. No contradicting evidence has subsequently emerged and, therefore, the earlier conclusions and recommendations are still valid.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Term of Reference 3 (TOR3) requested a review of the control measures applied by affected MSs to control the spread of ASF in wild boar and to eradicate infection. In the previous reporting period (EFSA, ), this assessment was based on a spatiotemporally explicit individual‐based model approach in structured geographic landscapes. No contradicting evidence has subsequently emerged and, therefore, the earlier conclusions and recommendations are still valid.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous report (EFSA, ), an extensive literature review had been undertaken to study the efficacy of different methods to control ASF spread through reducing wild boar population densities. The review was updated in this reporting period, but no conflicting evidence was found.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations